Influence of drying techniques and growing location on the chemical composition of sweet pepper (Capsicum annuum L., var. Senise). Issue 11 (1st September 2019) - Speranza, Giovanna; Lo Scalzo, Roberto; Morelli, Carlo F.; Rabuffetti, Marco; Bianchi, Giulia
Abstract: The aim of this work was the comprehensive characterization of dried Senise pepper, a tasty landrace, to verify the suitability of common industrial processing and different growing locations to its production. Fruits from experimental CREA fields of Battipaglia (southern Italy) and Montanaso (northern Italy), dried using a solar dryer or a forced air oven, were compared with lyophilized and commercial samples. Solar dried samples showed a retention of glucose, while fructose levels decreased. Citric acid was the main acid in all samples, showing a differentiated behavior upon processing, with higher content in Battipaglia samples. The ascorbic acid showed the highest correlation with antioxidant assays, and both drying methods decreased its content, with better retention in Battipaglia samples. Drying did not markedly affect carotenoid levels, showing higher content in Battipaglia peppers. Both drying technique and mostly growing location influenced the volatile profile, with higher apocarotenoid content in Battipaglia samples. Practical applications: The use of Senise red pepper, a tasty landrace awarded in 1996 with the PGI certification mark, is spreading even outside Italy due to the renewed interest for high quality products with excellent taste and healthy properties. These peppers are mostly sun‐dried following a traditional procedure and consumed as spice. New approaches regarding the type of drying and the growing location of this spice, together with the knowledge about the changes in quality indexes with processing, can be useful for a better exploitation of this product, increasing its market availability and lowering the cost of production.